The politics of Central Europe - Ágh, Attila (Sage, 1998)
This book provides a thorough introduction to East Central Europe and its renewed emergence since the momentous changes in the former Soviet bloc. By carefully differentiating between Central Europe, East Central Europe and the Balkans, Attila [ac]Agh shows how the term Èastern Europe' was a political misnomer of the Cold War. Drawing on theories of democratization to develop a common conceptual and theoretical framework, this textbook is the first to place the political and social changes of this complex region in a genuinely comparative perspective. Through broad thematic sections the stude.
Keywords: Europe, Eastern -- Politics and government -- 1989-; Europe, Central -- Politics and government -- 1989-; Post-communism -- Europe, Eastern.; Post-communism -- Europe, Central.; Democratization -- Europe, Eastern.; Democratization -- Europe, Central.; Europe de l'Est -- Politique et gouvernement -- 1989-; Europe centrale -- Politique et gouvernement -- 1989-; Postcommunisme -- Europe de l'Est.; Postcommunisme -- Europe centrale.; Démocratisation -- Europe de l'Est.; Démocratisation -- Europe centrale.; POLITICAL SCIENCE -- Political Process -- General.; Democratization; Politics and government; Post-communism; Central Europe; Eastern Europe; Politieke ontwikkeling.; Since 1989